Integrasi Nilai Budaya Ternate dalam Layanan Konseling untuk Mendukung Kesehatan Mental Siswa Multietnis - Hasrul Hasrul (Universitas Mathla'ul Anwar Banten, 2026)
This study aims to conduct a critical review and provide a conceptual framework regarding the integration of Ternate cultural values into counseling services to support the mental health of multiethnic students in schools. This research procedure follows the basic idea of a qualitative approach with a narrative literature review (NLR) method through four stages. The data source for this research is scientific articles obtained through the main Google Scholar database with a search period of 2005 to 2025. The results of the synthesis of 10 articles that met the inclusion criteria showed that, so far, the integration of cultural values in counseling services has been very diverse among researchers, but most still use counseling approaches and techniques based on the Western context. Another finding of this study is that Ternate cultural values, in the form of old proverbs (the Dalil Moro and Dola Bololo sentences), social traditions, and stories, have the potential to be integrated into counseling services that are more contextual and tailored to the characteristics of students in Ternate. To integrate local cultural values into effective counseling services to support student mental health, counselors or researchers can use eclectic counseling techniques (metaphor techniques).